Translation, Adaptation, and Validation of the Malay Version of the Cardiac Rehabilitation Barriers Scale - Chai, Li Sze; Sidiah, John Siop; Zabidah, Putit; Lily, Lim; Azylina, Gunggu; Tie, Suk Fong (Wolters Kluwer Health, Taiwan Nurses Association, 2020)
Background: The rate of cardiac rehabilitation attendance at the Sarawak Heart Centre was identified as very low, and the reason has not been investigated. A scale is needed to identify barriers to participation in cardiac rehabilitation among patients with heart disease in Sarawak, Malaysia.